2022
DOI: 10.1073/pnas.2110328119
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of force-pCa relation in MYL2 cardiomyopathy mice: Role of the super-relaxed state of myosin

Abstract: In this study, we investigated the role of the super-relaxed (SRX) state of myosin in the structure–function relationship of sarcomeres in the hearts of mouse models of cardiomyopathy-bearing mutations in the human ventricular regulatory light chain (RLC, MYL2 gene). Skinned papillary muscles from hypertrophic (HCM–D166V) and dilated (DCM–D94A) cardiomyopathy models were subjected to small-angle X-ray diffraction simultaneously with isometric force measurements to obtain the interfilament lattice spacing and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 45 publications
6
50
0
Order By: Relevance
“…The ST-RLC co-domain interactions (characteristic to a destabilized SRX in FHC) are not detected at the highest significance level in DCM or LVN species again implying their C-terminus SNVs are SRX detectors but not disruptors such that the MYBPC3 C-terminus segment SNVs do not influence SRX stability. The DCM result agrees with a previous analysis of myosin variants [34, 35]. The 2D-CG map for FHC SNVs appears to eliminate the free head (Level 1)-RLC (Level 3) contact destabilizing the SRX conformation.…”
Section: Discussionsupporting
confidence: 90%
“…The ST-RLC co-domain interactions (characteristic to a destabilized SRX in FHC) are not detected at the highest significance level in DCM or LVN species again implying their C-terminus SNVs are SRX detectors but not disruptors such that the MYBPC3 C-terminus segment SNVs do not influence SRX stability. The DCM result agrees with a previous analysis of myosin variants [34, 35]. The 2D-CG map for FHC SNVs appears to eliminate the free head (Level 1)-RLC (Level 3) contact destabilizing the SRX conformation.…”
Section: Discussionsupporting
confidence: 90%
“…Small-angle X-ray diffraction patterns in D94A papillary muscle fibers at submaximal Ca 2+ concentrations showed reduced I 1,1 / I 1,0 compared to controls, supporting the hypocontractile state of the D94A myosin motors including a reduced calcium sensitivity of force. In a follow up study [ 50 ], X-ray diffraction patterns were collected as a function of calcium activated force to generate full I 1,1 /I 1,0 -pCa curves, but the structure/function-pCa data were similar to WT indicating that the D94A mutant does not result in a shift of the equilibrium of relaxed heads from the OFF to ON states, consistent with the observed increased SRX population relative to wild type at rest. Myosin Binding protein C and DCM …”
Section: X-ray Diffraction Studies Of Muscle Diseasementioning
confidence: 83%
“…These differences in sarcomere structure were partially or fully reversed by pseudo-phosphorylation of D166V fibers from homozygous and heterozygous S15D-D166V mice, respectively, indicating that pseudo-phosphorylated RLC in the hearts of HCM mice is sufficient to prevent the development of the HCM phenotype. In a follow up study [ 50 ], the investigators showed that both of force/pCa (Ca 2+ -sensitivity) and lI 1,1 /I 1,0 -pCa were left shifted in HCM-D166V myocardium so that over most of the submaximal activation range, cross-bridges were closer to actin-containing thin filaments facilitating activation. These results accorded with biochemical assays where the population of myosin heads in SRX were reduced indicating that SRX-to-DRX transitions are promoted in HCM-D166V mutant myocardium consistent with the phenotype of hypercontractility characteristic of HCM.…”
Section: X-ray Diffraction Studies Of Muscle Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This unique relaxed state has come to be widely known as the “super-relaxed state” (SRX) (see reviews and references therein: e.g., Cooke, 2011 ; McNamara et al, 2015 ; Irving, 2017 ; Spudich, 2019 ; Craig and Padrón, 2022 ). SRX is reportedly in equilibrium with the disordered-relaxed state (DRX) in which myosin heads are in closer proximity to thin filaments (e.g., Anderson et al, 2018 ; Gollapudi et al, 2021 ; Yuan et al, 2022 ), and ready to produce force. A decrease in the number of myosin molecules in SRX would increase the proportion of the heads available to form force-generating cross-bridges (e.g., Schmid and Toepfer, 2021 ).…”
Section: Discussionmentioning
confidence: 99%